Register til nytte eller besvær, hva vet vi etter fem år? Etablering av et kvalitets- og forskningsregister for hukommelsesklinikker i spesialisthelsetjenesten - Nåvik, Marit; Engedal, Knut; Ulstein, Ingun (Nordisk Tidsskrift for Helseforskning, 2014)
Patient Registry, useful or not? What have we learned after five years?Background and aims: A patient registry was established in January 2009 to improve the quality of assessment and treatment of dementia at memory clinics in the South-Eastern and Western Health Regions of Norway. Further aims were to examine the validity of cognitive tests used in the assessment of dementia, to obtain new knowledge about risk factors and the course of dementia, treatment with and without antidementia medication, and to identify risk factors for developing neuropsychiatric symptoms and severe carer burden and burn-out. Data was also collected for epidemiological and clinical research.. In this article we will present our experiences regarding the process of developing and establishing the register. Methods: To evaluate the process of developing the register we have used The Wheel of Continuous Improvement, as it is presented the Norwegian strategy plan for quality improvement in the social and health service with the steps: plan, do, check and action (Veileder IS-1162. SHdir 2005). Results: In 2013 we have included 2220 patients in the register. The number of participating memory clinics has increased from 7 in 2007 to 15 in 2013. The participating memory clinics have included data from patients with different characteristics with regard to age, diagnoses and degree of cognitive impairment. Data from the register is used in ten research studies. Conclusions: It has been possible to establish a dementia register with patients data from 15 memory clinics in Norway that have  agreed to use a standard assessment battery for dementia. To motivate personal from the memory clinics to maintain collecting data, meetings, seminars and presenting results from each unit are of importance.